Identification of clinical outcomes from University of Carabobo Orthodontic Residency program based on american board of orthodontic cast criteria - Mejías Rotundo, Oswaldo Jesús (Venezuela, 2017)
The aim of this investigation was to identify treatment outcomes from University of Carabobo Orthodontic Residency program using American Board of Orthodontic’s Objective Grading System. Twenty five consecutive final dental cast were score for alignment, marginal ridges, bucolingual inclination, overjet, interproximal contacts, oclussal relationship and contacts. Normal distribution and t-test using 25 pts. for total score was applied with a P = 0.05 significance level. Results showed a mean score of 22,160 (CI 18,43 - 25,89). Alignment, bucolingual inclination and overjet had the means highest scores (3,52; 4,72; 4,56). P-value of 0,1291 showed no statistical difference from score reference of 25 pts. In conclusion, orthodontic residency students have clinical skills to finish patients with the requirements of phase 2 of american board of orthodontic exam. Determination of initial severity and an update in finishing protocol from cases attending the program are valid tools to improve scores of aforementioned variables.
Identificacion de resultados clinicos del postgrado de Ortodoncia de la Universidad de Carabobo basado en los criterios para modelos del Consejo Americano de Ortodoncia
Keywords: Treatment outcome; Orthodontics; Reference standars; Universities; Facultad de Odontología; Resultado del tratamiento; Ortodoncia; Estándares de referencia; Universidades; Revista Odontológica de Los Andes; Revista Odontológica de los Andes: Trabajos de Investigación; Medicina y Salud; Revistas